COVID-19 pandemic and quality of life among Romanian athletes - Cosma, G.-A.; Chiracu, A.; Stepan, A. R.; Cosma, M. A.; Nanu, M. C.; Voinea, F.; Bibi, K. W.; Paunescu, C.; Haddad, M. (International Journal of Environmental Research and Public Health, 2021)
The aim of this study was to analyze athletes` quality of life during the COVID-19 pandemic. The study involved 249 athletes between 15 and 35 of age, M = 21.22, SD = 5.12. The sample was composed of eight Olympic Games medalists, three European medalists, 67 international medalists, and 63 national medalists. The instruments used were: (1) COVID-19 Anxiety Scale, (2) Athlete Quality of Life Scale, (3) Impact of Pandemic on Athletes Questionnaire, and (4) International Personality Item Pool (IPIP Anxiety, Depression, and Vulnerability Scales). The results indicate significant differences in COVID-19 anxiety depending on the sport practiced, F (9239) = 3.81, p < 0.01, showing that there were significant differences between sports. The negative impact of the COVID-19 pandemic mediates the relationship between trait anxiety and the athletes` quality of life. The percentage of mediation was 33.9%, and the indirect effect was -0.11, CI 95% (-0.18, -0.03), Z = -2.82, p < 0.01. Trait anxiety has an increasing effect on the intensity of the negative impact of the COVID-19 pandemic, 0.23, CI 95% (.10, 0.35), Z = 3.56, p < 0.01, and the negative impact of the COVID-19 pandemic has a decreasing effect on quality of life, -0.47, CI 95% (-0.67, -0.27), Z = -4.62, p < 0.01. Gender and age did not moderate the relationship between the negative impact of COVID-19 and athletes` quality of life. The results of the study highlighted the impact that social isolation and quarantine have on athletes` affective well-being.